2004
DOI: 10.1128/iai.72.9.5253-5261.2004
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of theBacillus cereusGroup as Determined by Sequence Analysis of Six Housekeeping Genes and theplcRGene

Abstract: The population structure of the Bacillus cereus group (52 strains of B. anthracis, B. cereus, and B. thuringiensis) was investigated by sequencing seven gene fragments (rpoB, gyrB, pycA, mdh, mbl, mutS, and plcR). Most of the strains were classifiable into two large subgroups in six housekeeping gene trees but not in the plcR tree. In addition, several consistent clusters were identified, which were unrelated to species distinction. Moreover, interrelationships among these clusters were incongruent in each gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 37 publications
(50 reference statements)
4
72
0
Order By: Relevance
“…However, it does not appear possible to establish a strict correlation between the four pherotypes that we have defined in this study and the phylogenetic trees based on the analysis of housekeeping genes. This conclusion is in agreement with the absence of a phylogenetic relation between plcR and housekeeping genes, as indicated by a recent MLST study (13). The lack of congruence between pherotypes and phylogenetic classifications has previously been observed for the competence quorum-sensing system in B. subtilis (27) and for the Agr system in Staphylococcus species (3).…”
supporting
confidence: 76%
“…However, it does not appear possible to establish a strict correlation between the four pherotypes that we have defined in this study and the phylogenetic trees based on the analysis of housekeeping genes. This conclusion is in agreement with the absence of a phylogenetic relation between plcR and housekeeping genes, as indicated by a recent MLST study (13). The lack of congruence between pherotypes and phylogenetic classifications has previously been observed for the competence quorum-sensing system in B. subtilis (27) and for the Agr system in Staphylococcus species (3).…”
supporting
confidence: 76%
“…After calculating the I A for the entire collection and detecting lineages in the clusters corresponding to our C and T clusters, Helgason et al (16) and Priest et al (26) concluded that the whole Bacillus cereus group has a clonal or weakly clonal population structure. Ko et al (19) discovered an unusual feature of the plcR gene, presumably related to its horizontal transfer. Our work is original in that we studied a large number of strains isolated from a very limited geographical location (a forest near Versailles).…”
Section: Discussionmentioning
confidence: 99%
“…Results are indicated in Table S2 in the supplemental material. For four gene combinations (dnaA-mutS, dnaA-tul4, dnaA-fopA, and tpiA-fopA), significant conflict between data sets was indicated by P values below the recommended threshold of 0.05 (4,8,15). When strains F59, F60, and F62 were excluded from these analyses, all P values were above 0.05 (not shown).…”
mentioning
confidence: 99%